Lightweight Design of Formula Racing Sprocket based on Topology Optimization Method - Jixiong Li; Jianliang Tan; Guojie Mai (Jixie chuandong)
Abstract In order to obtain lightweight formula racing sprocket， the topological optimization method is introduced into the design of sprocket structure， the mathematical model of lightweight optimization design is constructed， and the geometric model of initial sprocket design is optimized by reducing the weight three times， and the sprocket with 49.59% mass reduction is obtained. Finally， the optimized model is processed and manufactured with the simulated check for strength， safety factor and life， and the prototype is fabricated and assembled into the racing car. The physical experiments are carried out on the racing car. The results show that the sprocket optimized meets the working requirements.